(untitled) (Eurasian Medical Research Periodical, 2023)
The growth of traffic flows, industry, as well as changes in the socio-spiritual life of society lead to an increase in the frequency and severity of injuries. In this article highlights tactics of treatment of fractures of tubular bones.